The Jewish Autonomous Region of Birobidzhan in Siberia - Vitale, Alessandro (European Spatial Research and Policy, 2021)
The Jewish Autonomous Region (JAR) of Birobidzhan in Siberia is still alive. The once famous “Siberian Zion”, at the confluence of the Bira and Bidzhan rivers, a stone’s throw away from China and a day from the Pacific Ocean, 9,000 km and six days by train from Moscow, is still a geographical reality. The political class of the Soviet Union decided to create a territory the size of Belgium for a settlement for Jews, choosing a region on the border between China and the Soviet Union. It believed that Soviet Jews needed, like other national minorities, a homeland with a territory. The Soviet regime thus opted to establish an enclave that would become the JAR in 1934. We should note that the creation of the JAR was the first historically fulfilled case of building an officially recognised Jewish national territory since antiquity and well before Israel. Nevertheless, many historians declared this experiment a failure and the history of the Region only tragic. It is interesting to note, however, that the survival of the JAR in post-Soviet Russia has been not only a historical curiosity, a legacy of Soviet national policy, but today – after the collapse of the Soviet Union – it represents a very interesting case study. It is also a topic useful for the analysis and understanding of inter-ethnic relations, cooperation, and coexistence and it is a unique case of geographic resettlement that produced a special case of “local patriotism”, as an example also for different ethnic groups living in the JAR, based on Jewish and Yiddish roots.